From Vision to Impact: A Strategic Framework for Principal Leadership in Professional Learning Communities - Triyastuti, Novitasari; Nurkolis, Nurkolis; Ariyanto, Lilik (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
Professional Learning Communities (PLCs) have the potential to improve teacher competency and learning quality, yet little research examines the strategic role of principals in their management. This study examines how principals formulate, implement, and evaluate strategies to optimise PLCs. This study employed a qualitative case study approach. Data were collected through observation, semi-structured interviews, and document analysis, then analysed using the Miles and Huberman interactive model and triangulation. The results indicate that during the formulation stage, principals conducted a needs analysis, established a shared vision and long-term goals, and conducted a SWOT analysis. The implementation stage emphasised direct leadership, empowering leading teachers, providing facilities and standard operating procedures (SOPs), and effective communication. Evaluation was conducted formally and informally with stakeholders using measurable indicators that support sustainability and quality improvement. This strategy fosters collaborative habits, enhances teacher professionalism, and improves learning quality. This study contributes theoretically by linking strategic management to PLC development and offers a practical, replicable model.